Autoguérison et minimalisme thérapeutique dans la France des années 1920 - Hervé Guillemain (Revue d'anthropologie des connaissances)
The Coué méthod is a practice of self-healing distributed worldwide from the 1920s. Relied on the curative role of the imagination, inspired by the practices of the nineteenth century, it represents a new form of self education, both body and mind. This study is based on the letters of the patients of the method to describe the different ways of appropriating this ideal of universal healing without mediation and without technology.